THE EFFECT OF INFLATION, INVESTMENT, GOVERNMENT EXPENDITURE AND POVERTY ON ECONOMIC GROWTH IN INDONESIA - Juliansyah, Hijri; Faisal, Mhd; Rahmah, Mutia; Khairisma, Khairisma; Yulis Terfiadi, Sari; Abbas, Tarmizi; Zulfahmi, Zulfahmi (CV. Radja Publika, 2022)
This study aims to determine the effect of Inflation, Investment, Government Expenditure and Poverty on Economic Growth in Indonesia in 1999 - 2020. This study uses secondary data for 1999-2020 obtained from the Indonesian Central Statistics Agency, NSWI BKPM, APBN KEMENKEU. The data is analyzed using the Vector Error Correction Model (VECM). The results showed that, in the short run, inflation did not significantly affect economic growth. But in the long run it did have a positive effect on economic growth. In the short run, the investment did not affect economic growth, but in the long run it did have a positive and significant effect on economic growth. The government expenditure in the short run did not affect economic growth, while in the long run government expenditure did have a negative and significant effect on economic growth. Finally, both in short run and long run, poverty did not affect economic growth in Indonesia.